The Comparison of Premises for Recognizing Tax Books as Kept not Compliant in the Tax Law and Accounting Law in Poland - Witczak, Radosław (Journal of Finance and Financial Law, 2022)
The purpose of this article. The purpose of the paper is to compare and assess provisions on premises for recognizing tax books as kept not compliant to the regulations in the tax law and accountancy law as well as to discuss the possibility of using the tax judgments on this issue in the interpretation of compliant account books in the accountancy law. The research hypothesis is as follows: The tax judgments on the premises for recognizing tax books as kept not compliant may be also used directly for the interpretation of compliancy of account books in the accountancy law. Methodology. The descriptive study including critical attitude to the legal acts and literature was used to solve the research problem. The result of the research. Both the tax law and accountancy law comprise the rules for recognizing tax books (account books) to be compliant to the regulations. The tax law uses the terms of the reliability and correctness. The Accountancy Act law uses the terms of the reliability, error-free, verifiable manner and on an on-going basis. Although definitions of reliability are very similar, as the analysis shows, the character of reliability of tax books is not always the same as for account books. The judgments in the field of interpretation of the reliability for tax purposes may not always be used for accounting purposes. The term correctness in the Tax Ordinance does not always correspond to the terms: error-free, verifiable manner and on an on-going basis in the Accountancy Act. So, the tax judgment concerning correctness of the tax book from the tax law cannot be directly applied into the interpretation of such terms as error-free, verifiable manner and on an on-going basis in the accountancy law. The paper additionally proposes some changes to the tax law concerning the unreliability of tax books, as well as changes to the Accountancy Act.